ANTRENÖRLERİN ALGILANAN STRES DÜZEYLERİ, ÖZ YETERLİLİKLERİ VE YAŞAM DOYUMLARININ BAZI DEĞİŞKENLER AÇISINDAN İNCELENMESİ - PAMUKCU, ENES (Fırat Üniveristesi, 2022)
Bu araştırma antrenörlerin algılanan stres düzeyleri, öz yeterlilikleri ve yaşam doyumlarının bazı değişkenler (yaş, cinsiyet, medeni durum, eğitim durumu, aylık gelir, antrenörlük yılı, antrenörlük dalı) açısından incelenmesi ve bu değişkenlere göre farklılaşmanın olup olmadığını belirlemek amacıyla yapılmıştır. Araştırmanın evrenini Elazığ ilinde yer alan antrenörler oluştururken örneklemini ise tesadüfi örneklem yöntemiyle seçilen 156 kişi oluşturmuştur. Araştırma kapsamında verilerin toplanması için "Kişisel Bilgi Formu", "Algılanan Stres Ölçeği", "Genel Öz yeterlilik Ölçeği" ve "Yaşam Doyumu Ölçeği" kullanılmıştır. Verilerin değerlendirilmesinde SPSS 24 paket programı kullanılıp elde edilen verilerin analizinde demografik bilgiler için frekans ve yüzde, kolmogorov-smirnov sonuçlarına göre parametrik olan testlerden, ikili gruplar için T testi, çoklu gruplar için tek yönlü varyans analizi (Anova), gruplar arası farklılıkların belirlenmesinde ise Tukey testi uygulanmıştır. Araştırmaya katılan antrenörlerin %26.9'u 18-25 ve 26-33 yaş aralığında, %62.8'inin erkek, %52.6'sının ise bekar olduğu, %70.5'inin ön lisans-lisans mezunu, %48.7'sinin aylık gelir durumunun 5001 tl ve üzerinde olduğu, antrenörlük sürelerine bakıldığında ise %52.6'sının 1-5 yıl arasında ve %50.6'sının da takım sporları antrenörlüğü yaptığı görülmüştür. Sonuç olarak, çalışmaya katılan antrenörlerin yaş, aylık gelir ve antrenörlük süreleri arttıkça yaşam doyumlarının arttığı, kadın katılımcıların stres algılarının daha yüksek olduğu, erkek katılımcıların daha yüksek öz yeterliliğe ve yaşam doyumuna sahip olduğu görülmüş ve evli olan antrenörlerin yaşam doyumlarının bekar olan antrenörlerden daha yüksek olduğu tespit edilmiştir.

Investigation of Perceived Stress Levels, Self-Efficacy and Life Satisfaction of Coaches Based on Certain Variables This study was conducted to investigate the perceived stress levels, self-efficacy, and life satisfaction of coaches in terms of certain variables (age, gender, marital status, educational status, monthly income, years of coaching, coaching branch) and to determine whether there were differences in terms of these variables. The population of the study was composed of coaches located in the city of Elazig while the sample consisted of 156 individuals chosen by the random sampling method. "Personal Information Form", "Perceived Stress Scale", "General Self-Efficacy Scale" and "Life Satisfaction Scale" were used to collect the data within the framework of the study. In the analysis of the data, SPSS 24 package software was used. In the analysis, frequency and percentage calculations were conducted for the demographic data while parametric tests, according to the Kolmogorov-Smirnov results, were conducted. Additionally, a t-test was conducted for paired groups while a One-way analysis of variance (ANOVA) was conducted for multiple group comparisons. The Tukey test was used to determine the differences between groups. Of the coaches participating in the study, 26.9% were between the ages of 18-25 and 26-33 while 62.8% of them were males in addition to 52.6% of the participants who were single. Furthermore, 70.5% of the participants had associate degrees-bachelor degrees while 48.7% of them had a monthly income of 5001 TL and above. In terms of the coaching times, it was observed that 52.6% of them served 1-5 years while 50.6% of the participants served as coaches of team sports. As a result, it was seen that the life satisfaction levels of the coaches participating in the study increased as the age, monthly income, and coaching time variables increased. It was also detected that the stress perceptions of the female participants were higher while the male participants had higher self-efficacy and life satisfaction levels. Finally, it was determined that the life satisfaction levels of the married coaches were higher than the single coaches.
Investigation of perceived stress levels, SELF-efficacy and life satisfaction of coaches based on certain variables
Keywords: Spor